Overview on Interpersonal Communication and Phenomenological Approaches in Health Care - Vimala, Govindaraju (International Journal Documentation & Research Institute (IJDRI), 2021)
Phenomenology is one of the qualitative research methodology approach. The phenomenological approach is concerned with the subjectivity of the observer, but does not have to be limited to the individual level. Phenomenologist are interested to share a similar understanding of the world and how to build intersubjective spheres. This is an implicit response to what the world looks like and is sometimes referred to as the life world. This article outlines phenomenological approaches related to health research. A phenomenological methodology that describes and directs experiences that apply specifically to a person's illness experience in order to clarify that experience and allow healthcare providers to better understand it. Healthcare interviews and observations allow researchers to identify and understand data from participants' living experiences using a phenomenological approach.